Aerobic Biodegradation of 2,4-Dinitroanisole by Nocardioides sp. Strain JS1661 - Fida, Tekle Tafese (Appl Environ Microbiol, 2014)
2,4-Dinitroanisole (DNAN) is an insensitive munition ingredient used in explosive formulations as a replacement for 2,4,6-trinitrotoluene (TNT). Little is known about the environmental behavior of DNAN. There are reports of microbial transformation to dead-end products, but no bacteria with complete biodegradation capability have been reported. Nocardioides sp. strain JS1661 was isolated from activated sludge based on its ability to grow on DNAN as the sole source of carbon and energy. Enzyme assays indicated that the first reaction involves hydrolytic release of methanol to form 2,4-dinitrophenol (2,4-DNP). Growth yield and enzyme assays indicated that 2,4-DNP underwent subsequent degradation by a previously established pathway involving formation of a hydride-Meisenheimer complex and release of nitrite. Identification of the genes encoding the key enzymes suggested recent evolution of the pathway by recruitment of a novel hydrolase to extend the well-characterized 2,4-DNP pathway.